Surface Modification of Nickel Sulfide Nanoparticles: Towards Stable Ultra‐Dispersed Nanocatalysts for Residue Hydrocracking. Issue 8 (29th March 2016) - Du, Hui; Liu, Dong; Wu, Hao; Xia, Wei; Zhang, Xiaodong; Chen, Zhaojun; Liu, Yongjiu; Liu, Hualong
Abstract: Ultra‐small nickel sulfide nanoparticles (NSNPs) of 5–8 nm are prepared by a reverse microemulsion route and then modified by oleic acid and 1‐dodecanethiol to replace the adsorbed surfactant. Experimental results reveal that the particle size and crystal structure of the NSNPs did not change significantly during the modification process. Different from the adsorption by the electrostatic attraction between the surfactant and NSNPs, oleic acid and 1‐dodecanethiol are adsorbed firmly on the NSNPs through chemisorption. Catalytic hydrocracking tests demonstrate that the surface modification enhances the hydrocracking activity of the NSNPs. The surfactant‐coated NSNPs disperse in toluene‐insoluble products in as agglomerates of 20–30 nm, whereas the modified NSNPs mainly disperse as their original size. The results prove that the chemisorption of oleic acid and 1‐dodecanethiol on NSNPs remains steady and maintains the stable dispersion of NSNPs under high temperature and pressure. Abstract : Stable nanocatalysts : The chemisorption of oleic acid (OA) and 1‐dodecanethiol (DDT) on nickel sulfide nanoparticles (NSNPs) remains steady and the stable dispersion of NSNPs is maintained under harsh hydrocracking conditions of high temperature and pressure, which improves the anticoking performance of NSNPs. CTAB=Cetyltrimethyl ammonium bromide.